Design and Properties of New Lead-Free Solder Joints Using Sn-3.5Ag-Cu Solder - Shalaby, Rizk Mostafa; Kamal, Mustafa; Ali, Esmail Abdo Mohammed; Gumaan, Mohammed S. (Springer Nature, 2018)
This article aims to reduce the melting temperature of lead-free solder alloy and promote its mechanical properties. Eutectic tin-silver lead-free solder has a high melting temperature 221 ?C used for electronic component soldering. This melting temperature, higher than that of lead-tin conventional eutectic solder, is about 183 ?C. The effect of the melt spinning process and copper additions into eutectic Sn-Ag solder enhances the crystallite size to about 47.92 nm which leads to a decrease in the melting point to about 214.70 ?C, where the reflow process for low heat-resistant components on print circuit boards needs lower melting point solder. The results showed the presence of intermetallic compound Ag3Sn formed in nano-scale at the Sn-3.5Ag alloy due to short time solidification. The presence of new intermetallic compound, IMC from Ag0.8Sn0.2 and Ag phase improves the mechanical properties, and then enhances the micro-creep resistance especially at Sn-3.5Ag-0.7Cu. The higher Youngs modulus of Sn-3.5Ag-0.5Cu alloy 55.356 GPa could be attributed to uniform distribution of eutectic phases. Disappearance of tin whiskers in most of the lead-free melt-spun alloys indicates reduction of the internal stresses. The stress exponent (n) values for all prepared alloys were from 4.6 to 5.9, this indicates to climb deformation mechanism. We recommend that the Sn95.7-Ag3.5-Cu0.7 alloy has suitable mechanical properties, low internal friction 0.069, low pasty range 21.7 ?C and low melting point 214.70 ?C suitable for step soldering applications.